2014
DOI: 10.12968/denu.2014.41.5.449
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab-associated osteonecrosis of the jaw – a case report

Abstract: Osteonecrosis of the jaw (ONJ) following bisphosphonate use is well documented. However, to our knowledge, there are few cases reported on ONJ related to the use of other pharmaceutical agents, such as denosumab--a monoclonal antibody that is prescribed for the treatment of osteoporosis and is used as an anti-cancer agent. Here we present the first case in the UK of a patient who has developed ONJ following treatment with denosumab. The purpose of this report is to highlight the potential effects of this monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Since the first description by Taylor et al . 18 detailed cases of DRONJ have been reported in the English‐language literature (Table ) . Additional studies have focused on DRONJ, but detailed description of dosing and length of treatment, etiologic factors, and specific treatment protocols were not always provided .…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description by Taylor et al . 18 detailed cases of DRONJ have been reported in the English‐language literature (Table ) . Additional studies have focused on DRONJ, but detailed description of dosing and length of treatment, etiologic factors, and specific treatment protocols were not always provided .…”
Section: Discussionmentioning
confidence: 99%
“…Recent therapeutic strategies for treating bone metastasis include surgery, radiotherapy and osteoclast inhibitors, such as bisphosphonates and denosumab, the human monoclonal antibody used to neutralize RANKL. Regardless of the wide use of these treatments, radiotherapy should still be administered for symptom palliation (57), although bisphosphonates and denosumab can cause unfavorable side-effects, such as osteonecrosis of the jaw (11)(12)(13)(14). Based on these findings, new strategies for the treatment of bone metastases with fewer side-effects are required.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of these treatment modalities remain limited. In addition, osteonecrosis of the jaw and hypocalcemia represent serious side-effects and long-term prognosis associated with these treatments remains unknown (11)(12)(13)(14).…”
Section: Transcutaneous Carbon Dioxide Application Suppresses Bone Dementioning
confidence: 99%
“…By contrast, Diz et al (12) reported a case of denosumab-related ONJ due to tooth extraction 6 months after cessation of denosumab therapy. Notably, Vyas et al (38) reported a case of denosumab-related ONJ that healed within 1 month of cessation of denosumab. Thus, it is difficult to determine the appropriate period of a drug holiday for denosumab.…”
Section: Discussionmentioning
confidence: 99%